An overview of 20 years of genetic studies in pheochromocytoma and paraganglioma. Issue 2 (March 2020) - Buffet, Alexandre; Burnichon, Nelly; Favier, Judith; Gimenez-Roqueplo, Anne-Paule
Abstract : Paragangliomas and pheochromocytomas (PPGL) are rare neuroendocrine tumours characterized by a strong genetic determinism. Over the past 20 years, evolution of PPGL genetics has revealed that around 40% of PPGL are genetically determined, secondary to a germline mutation in one of more than twenty susceptibility genes reported so far. More than half of the mutations occur in one of the SDHx genes ( SDHA, SDHB, SDHC, SDHD, SDHAF2 ), which encode the different subunits and assembly protein of a mitochondrial enzyme, succinate dehydrogenase. These susceptibility genes predispose to early forms ( VHL, RET, SDHD, EPAS1, DLST ), syndromic ( RET, VHL, EPAS1, NF1, FH ), multiple ( SDHD, TMEM127, MAX, DLST, MDH2, GOT2 ) or malignant ( SDHB, FH, SLC25A11 ) PPGL. The discovery of a germline mutation in one of these genes changes the patient's follow-up and allows genetic screening of affected families and the presymptomatic follow-up of relatives carrying a mutation.